The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/3161738
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized Ex Vivo Trial to Assess the Ideal Stapling Site for Endoscopic Fundoplication with Medigus Ultrasonic Surgical Endostapler

Abstract: Background and Aims. Endoscopic fundoplication is an emerging technique for the treatment of gastroesophageal reflux disease (GERD). The aim of this study is to determine the ideal position of the staples in relation to gastroesophageal junction (GEJ). Methods. Ten endoscopic fundoplication procedures were performed in each group using fresh ex vivo porcine stomachs: Group A: 2 staples each at 3 cm above the GEJ and 180° apart; Group B: 2 staples at 3 cm and 90° apart; Group C: 2 staples at 4 cm and 180° apart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…MUSE creates a 180°f undoplication by stapling the gastric fundus to the esophagus below the diaphragm under ultrasound guidance. TIF by MUSE was first tested in animal studies and ex vivo models [3,4]. In a multicenter study, the technique was found to be safe and effective up to 4 years [5].…”
Section: Introductionmentioning
confidence: 99%
“…MUSE creates a 180°f undoplication by stapling the gastric fundus to the esophagus below the diaphragm under ultrasound guidance. TIF by MUSE was first tested in animal studies and ex vivo models [3,4]. In a multicenter study, the technique was found to be safe and effective up to 4 years [5].…”
Section: Introductionmentioning
confidence: 99%
“…An early study using porcine models, found that the endoscopic anterior fundoplication was intact in 12 pigs during post-sacrifice autopsy who underwent the procedure at 2, 4 and 6 weeks prior ( 28 ). An ex-vivo study, performing MUSE fundoplication on porcine esophagus and stomach, demonstrated good reflux control with significantly higher intragastric pressures required to detect stomach contents (methylene blue dyed normal saline), in the esophagus ( 29 ). Compared to the EsophyX device, the literature on MUSE outcomes is still sparse— there are very few small studies that exist to date.…”
Section: Endoscopic Procedures For Management Of Gerdmentioning
confidence: 99%
“…MUSE™ (Medigus, Omer, Israel) creates a 180° fundoplication by stapling the gastric fundus to the esophagus below the diaphragm under ultrasound guidance. TIF by MUSE™ was first tested in animal studies [11] and then in ex vivo models [12]. In three studies the technique was found safe and effective up to four years [5,6,13].…”
Section: Lesmentioning
confidence: 99%